The Semantic Field of Tazkiyah al-Nafs in the Qur’an: A Psychospiritual Framework for Islamic Psychology - Nur Ardhiansyah K. Ibrahim; Zulfi Fadhlurrahman; Farhani Azkia; Putri Salsabila Azkya (UIN Sunan Kalijaga Yogyakarta, 2026)
This article reconstructs the semantic field of tazkiyah al-nafs in the Qur’an as a conceptual foundation for Islamic psychology. It addresses a methodological problem in contemporary Islamic psychological discourse: tazkiyah is often used as a normative or therapeutic concept before its Qur’anic semantic structure has been carefully mapped. Combining thematic exegesis (tafsīr mauḍūʻī) with semantic-field analysis, the article examines the root z-k-w, its morphological distribution, contextual anchor loci, oppositional relations, and exegetical corroboration. It identifies QS al-Syams (91):7–10 as the primary structural locus of the field, where nafs, taqwā–fujūr, tazkiyah–tadsiyah, and falāḥ–khaibah are arranged in a layered moral structure. The study argues that tazkiyah cannot be reduced to purification alone. While taṭhīr primarily denotes the removal of impurity, tazkiyah includes purification and exceeds it through cultivation, growth, moral elevation, and teleological orientation toward falāḥ. By distinguishing tazkiyah from related concepts such as taṭhīr, taubah, and iṣlāḥ, the article offers a more precise Qur’anic account of moral formation. Its contribution is therefore pre-clinical and conceptual: it provides a Qur’anic semantic foundation for Islamic psychology without claiming to establish a finalized therapeutic model.